Biallelic PTCH1 Inactivation Is a Dominant Genomic Change in Sporadic Keratocystic Odontogenic Tumors. (April 2020) - Stojanov, Ivan J.; Schaefer, Inga-Marie; Menon, Reshma S.; Wasman, Jay; Gokozan, Hamza N.; Garcia, Elizabeth P.; Baur, Dale A.; Woo, Sook-Bin; Sholl, Lynette M.
Abstract : Keratocystic odontogenic tumors (KCOTs) are locally aggressive odontogenic neoplasms with recurrence rates of up to 60%. Approximately 5% of KCOTs are associated with nevoid basal cell carcinoma (Gorlin) syndrome and 90% of these show genomic inactivation of the PTCH1 gene encoding Patched 1. Sporadic KCOTs reportedly have PTCH1 mutations in 30% of cases, but previous genomic analyses have been limited by low tumor DNA yield. The aim of this study was to identify recurrent genomic aberrations in sporadic KCOTs using a next-generation sequencing panel with complete exonic coverage of sonic hedgehog (SHH) pathway members PTCH1, SMO, SUFU, GLI1, and GLI2 . Included were 44 sporadic KCOTs from 23 female and 21 male patients with a median age of 50 years (range, 10 to 82 y) and located in the mandible (N=33) or maxilla (N=11). Sequencing identified PTCH1 inactivating mutations in 41/44 (93%) cases, with biallelic inactivation in 35 (80%) cases; 9q copy neutral loss of heterozygosity targeting the PTCH1 locus was identified in 15 (34%) cases. No genomic aberrations were identified in other sequenced SHH pathway members. In summary, we demonstrate PTCH1 inactivating mutations in 93% of sporadic KCOTs, indicating that SHH pathway alterations are a near-universal event in these benign but locally aggressive neoplasms. The high frequency of complete PTCH1 loss of function may provide a rational target for SHH pathway inhibitors to be explored in future studies.